Analisis Rencana Implementasi dengan Metode EOQ Pada Manajemen Persediaan Material - Fajar Mustafa Tiloly; Resista Vikaliana; Irwansyah Irwansyah (Journal of Business and Economics Research (JBE), 2022)
Inventory of raw materials or materials at PT. PGP has not been planned properly so that one time the raw materials run out during the production process. Inventory management applied by the company has not paid attention to the economical order quantity, and also the point of reordering the raw materials. This of course has an impact on additional costs that should not be needed, in other words it is not effective and efficient, so that PT. PGP sees the need to apply the EOQ method in managing raw materials. This study aims to determine the application of the Economic Order Quantity (EOQ) method to the control of raw material inventory at PT PGP. This study uses quantitative methods with the object of research at PT. PGP. The sample of this study used company inventory data in 2019 – 2020, which was taken using the purposive sampling method. The results showed a 59% reduction in costs. Initially, with the company's current policy, the total cost is Rp. 14,389,750.00 and when using the EOQ method it drops to Rp. 5,842,587.60. The presence of safety stock, reorder point, is also taken into account in this study. The results of the study prove that the EOQ method plays an important role in controlling raw material inventory at PT PGP.